Inflammation, Innate Immunity, and the Intestinal Stromal Cell Niche: Opportunities and Challenges - Owens, Benjamin M. J. (Frontiers in Immunology, 2015)
Stromal cells of multiple tissues contribute to immune-mediated protective responses and, conversely, the pathological tissue changes associated with chronic inflammatory disease. However, unlike hematopoietic immune cells, tissue stromal cell populations remain poorly characterized with respect to specific surface marker expression, their ontogeny, self-renewal and proliferative capacity within tissues and the extent to which they undergo phenotypic immunological changes during the course of an infectious or inflammatory insult. Extending our knowledge of the immunological features of stromal cells provides an exciting opportunity to further dissect the underlying biology of many important immune-mediated diseases, although several challenges remain in bringing the emerging field of stromal immunology to equivalence with the study of the hematopoietic immune cell compartment. This review highlights recent studies that have begun unraveling the complexity of tissue stromal cell function in immune responses, with a focus on the intestine, and proposes strategies for the development of the field to uncover the great potential for stromal immunology to contribute to our understanding of the fundamental pathophysiology of disease, and the opening of new therapeutic avenues in multiple chronic inflammatory conditions.